a DETEKSI DINI PRA HIPERTENSI PADA PEKERJA DI RS-FKIK UKRIDA DENGAN ANALISA HEART RATE VARIABILITY: DETEKSI DINI PRA HIPERTENSI PADA PEKERJA DI RS-FKIK UKRIDA DENGAN ANALISA HEART RATE VARIABILITY - Yuvensius Gerry Atmaja; Suparto Suparto; Ronald Winardi Kartika (Jurnal MedScientiae, 2023)
The global burden of disease study shows that stroke and ischemic heart disease are the main causes of death and disability in 2017. RISKESDAS 2018 showed that the prevalence of hypertension measured in residents over the age of 18 the increased from 25.8% to 34.1 This is the background of this study on early detection of prehypertension by analyzing heart rate variability in UKRIDA hospital staff. Data collection was performed by an objective sampling technique. There were 81 study samples that met the inclusion and exclusion criteria. As a result, the majority of respondents in the gender category were female, for a total of 43 respondents (53.1%). By age group, 44 people (54.3%) were in the age group of 20-30 years, the most. Subsequently, 29 of her in the professional group were nurses (35.8%). Most of the respondents were normotensive, i.e. 41 respondents (50.6%), and most of the SDNN respondents were of normal height, even 31 respondents (28.4%). The majority of respondents are RSMDD, or normal high, with as many as 23 (28.4%) respondents. HRV influences early detection of prehypertension by SDNN and RMSDD blood pressure results when the correlation test is 0.00 (p-value < 0.05).